Design for/by "The Global South". Issue 1 (2nd January 2017) - Fry, Tony
Abstract: The aim of this essay is to contribute to the development of a paradigmatic shift in how design is understood, transformed and practiced in the Global South. It does this by establishing the case for building a strong contextual relation between design, colonialism, and the mobilised counter-agency of decoloniality. Thereafter, design for/by the Global South is presented within a critical epistemological reframing subordinate to a situated imperative of the 'Sustainment'.